2009
DOI: 10.1103/physrevd.80.023503
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic age, statefinder, andOmdiagnostics in the decaying vacuum cosmology

Abstract: As an extension of ΛCDM, the decaying vacuum model (DV) describes the dark energy as a varying vacuum whose energy density decays linearly with the Hubble parameter in the late-times, ρ Λ (t) ∝ H(t), and produces the matter component. We examine the high-z cosmic age problem in the DV model, and compare it with ΛCDM and the Yang-Mills condensate (YMC) dark energy model. Without employing a dynamical scalar field for dark energy, these three models share a similar behavior of late-time evolution. It is found th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
67
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 87 publications
0
67
0
Order By: Relevance
“…The Om(z) diagnostic [39] has been proposed to differentiate C DM to other DE models. Many authors [71][72][73] have studied the DE models based on Om(z) diagnostic. Its constant behaviour with respect to z represents that DE is a cosmological constant ( C DM).…”
Section: Om Diagnosticmentioning
confidence: 99%
“…The Om(z) diagnostic [39] has been proposed to differentiate C DM to other DE models. Many authors [71][72][73] have studied the DE models based on Om(z) diagnostic. Its constant behaviour with respect to z represents that DE is a cosmological constant ( C DM).…”
Section: Om Diagnosticmentioning
confidence: 99%
“…This distinguishing method is a geometrical diagnosis in a model-independent manner and in principle needs high-precision observational data. Since different DE models exhibit different evolution trajectories in the r -s plane, especially being separated distinctively with the values of {r 0 , s 0 }, the statefinder can be used to diagnose different DE models [47][48][49][50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…Some works [38][39][40][41][42][43][44][45][46][47] revealed that the statefinder diagnostic can effectively discriminate various DE models and break/differentiate the degeneracies between different parameter values of DE model, except for a few models (for example, the new agegraphic DE model [45,47]). Furthermore, Arabsalmani and Sahni [48] introduced the statefinder hierarchy and the growth rate of linear perturbations as "null diagnostics" for the ΛCDM model.…”
mentioning
confidence: 99%